1. KEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN DEMAKKEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN DEMAK - Wiwik Widayati (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Farmland conservation is regulated in law number 41 year 2009 with intention to conserve food area and farmland continuously and to ensure the availability of food farmland for the sake of creating independency, endurance and sovereignty of food. Continuous farmland conservation is exercised on continuous food farmland and reserve food farm, both within or outside the perimeter of food farmland. The policy of continuous food farmland does not stop on decreeing a land into a continuous food farmland, but also a series of activities which support and ensure the availability and conservation of the food farmland.